Country governance and international equity returns - Marshall, Ben R.; Nguyen, Hung T.; Nguyen, Nhut H.; Visaltanachoti, Nuttawat (Journal of Banking & Finance, 2021)
Monthly returns in countries with strong governance lead monthly returns in weak governance countries. This predictability holds in and out-of-sample at both the group and individual country levels. Moreover, the predictability is not fully explained by other related possible sources of cross-country predictability such as differences in country development, political risk, size, liquidity, short-selling constraints, the predictive ability of U.S. equity returns, or non-synchronous trading. It appears that equity returns in different countries react to value-relevant world information at different speeds based on their levels of country governance.